Pengembangan Lembar Kerja Peserta Didik Berbasis POE dalam Melatih Keterampilan Proses Sains pada Tema Pelestarian Lingkungan di SMP Kelas VII - Mimi Mas Nurika; Mudmainah Vitasari; Annisa Novianti Taufik (UNIB Press, 2022)
By linking the domains of science studies, the 2013 curriculum emphasizes integrated science study. Scientific learning is more than just memorizing information and concepts; it must be shown via experiments that allow students to apply science process skills. As part of the production of instructional materials, science process skills are taught. Such as LKPD, which is built on the predict, observe, and explain principle (POE). The goal of this study is to learn more about the creation process and degree of validation of POE-based LKPD training PPP on environmental conservation topics in grade VII SMP. The study was conducted utilizing a 3-D version of the 4-D Research and Development technique, particularly the Define, Design, and Develop stages. A validation questionnaire was filled out by two material expert lecturers, two media experts, and two junior high school science teacher practitioners for the study's instrument. The results showed that the development process used 3D development and that the POE-based LKPD had a level of validity of 90% for material experts with a very valid category, 72% for media experts with a valid category, and 90.5% for junior high school science teachers with a very valid category. The POE-based LKPD may be evaluated in scientific learning to develop science process skills, based on the recapitulation of the validation findings; all validators received an average percentage value of 84% in the extremely valid category.